PEMBUATAN KOMPOSTER MENGGUNAKAN SAMPAH ORGANIK DENGAN AKTIVATOR EM4 - Rochsun Rochsun; Dian Fitri Argarini; Dyah Ayu Sulistyaning Cipta; Dina Fitria Ramadani; Rohdiatin Artiani Ulla (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
Garbage becomes a problem, when waste is perceived as useless material, creates bad smells, is harmful to the environment, causes pollution to the surrounding environment, invites disease bacteria, kills marine life, spoils the view, and many other negative perceptions. One strategy for dealing with waste is to teach children at SMP Negeri 2 Wagir, Sukodadi Village, Wagir District, Malang Regency about turning waste into useful things, namely by making a simple composter using used bottles that function as a means of converting organic waste (leaves and paper) into solid and liquid fertilizers. This service activity focuses on organic waste that can be turned into compost (solid fertilizer and liquid fertilizer). The skill of making compost is actually simple, but it must be taught because it turns out that not many children know about it, let alone practice it in everyday life. The purpose of this activity is to study the method and process of making compost by means of anaerobic fermentation with the help of EM4 bioactivator as decomposing bacteria and brown sugar for bacterial food, and to determine optimal operating conditions in order to obtain maximum compost both qualitatively and quantitatively. The method in this activity goes through 5 stages, namely the first stage is presentation of the material, the second stage is the practice of making a simple composter using used bottles, the third stage is making composter liquid consisting of EM4 bioactivator, sugar and water, the fourth stage is mixing organic waste with composter liquid , the fifth stage is forcing the trash into the bottle. The results of the activities that have been carried out are training in making compost as a result of processing organic waste. Based on the activities that have been carried out, students are able to practice environmentally friendly waste management both at school and in everyday life.